A review of HIV in prisons in Nepal - Dolan, K; Larney, S (Kathmandu University Medical Journal, 2010)
Background: HIV in prisons is a serious public health concern. People in prison are at risk of contracting HIV through injecting drug use, unprotected sex and tattooing. However, most countries have largely neglected HIV prevention and care in prisons. Objectives: The aim of this study is to review HIV prevention and care in Nepal's prisons Materials and methods: This was carried out by Systematic review of published and grey literature. Results: Nepal's National HIV Strategy acknowledges the importance of prisons in broader HIV prevention efforts. However, prison conditions are poor and there is no accurate information regarding HIV prevalence or risk behaviours among prisoners. HIV prevention interventions have largely been limited to ad hoc training workshops. Antiretroviral treatment is not available to HIV infected prisoners. Conclusion: There is recognition in Government policy documents that prisons must be involved in efforts to stem the HIV epidemic. However, HIV prevention and care remains largely non-existent in Nepal's prisons. Efforts to obtain external funding to initiate and maintain programs such as drug dependency treatment and condom distribution are required. Attention could also be given to introducing alternatives to incarceration for less serious offenders and drug dependent offenders. Key words: HIV; prison; Nepal DOI: 10.3126/kumj.v7i4.2753 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 351-354